Non‐invasive UPR monitoring system and its applications in CHO production cultures. Issue 8 (26th March 2013) - Du, Zhimei; Treiber, David; McCoy, Rebecca E.; Miller, Amanda K.; Han, Mei; He, Feng; Domnitz, Sarah; Heath, Carole; Reddy, Pranhitha
Abstract Unfolded protein response (UPR) is the primary signaling network activated in response to the accumulation of unfolded and/or misfolded protein in the endoplasmic reticulum (ER). The expression of high levels of recombinant proteins in mammalian cell cultures has been linked to the increased UPR. However, the dynamics of different UPR‐mediated events and their impact on cell performance and recombinant protein secretion during production remain poorly defined. Here, we have created a non‐invasive UPR‐responsive, fluorescence‐based reporter system to detect and quantify specific UPR‐mediated transcriptional activation of different intracellular signaling pathways. We have generated stable antibody‐expressing CHO clones containing this UPR responsive system and established FACS‐based methods for real‐time, continuous monitoring of the endogenous UPR activation in live cultures. The results showed that the UPR activation is dynamically regulated during production culture. The clones differed in their UPR patterns; both the timing and the degree of UPR‐induced transcriptional activation were linked to cell performance, such as growth, and viability. In addition, the cell culture environment, such as media composition and osmolarity, significantly impacted endogenous UPR activation. Taken together, these data demonstrate a utility of this UPR monitoring system in recombinant protein production processes and the observations increase our understanding of the critical role of UPR in regulating diverse phenotypes of the cells including growth, survival and recombinant protein secretion under different culture environments and processing conditions. Biotechnol. Bioeng. 2013; 110: 2184–2194. © 2013 Wiley Periodicals, Inc.